2020
DOI: 10.3390/s20164394
|View full text |Cite
|
Sign up to set email alerts
|

Future-Frame Prediction for Fast-Moving Objects with Motion Blur

Abstract: We propose a deep neural network model that recognizes the position and velocity of a fast-moving object in a video sequence and predicts the object’s future motion. When filming a fast-moving subject using a regular camera rather than a super-high-speed camera, there is often severe motion blur, making it difficult to recognize the exact location and speed of the object in the video. Additionally, because the fast moving object usually moves rapidly out of the camera’s field of view, the number of captured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…A lot of work in AR with relation to speed or motion involves automatic object tracking or trajectory prediction (Chen and Meng, 2010;Gao and Spratling, 2022;Lee et al, 2020;Li et al, 2021;Morzy, 2006). Bedell et al investigated which judgment is perceived first, color change or movement, and found that it depends on motion cycle (Bedell et al, 2003).…”
Section: Color and Luminance As Depth Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of work in AR with relation to speed or motion involves automatic object tracking or trajectory prediction (Chen and Meng, 2010;Gao and Spratling, 2022;Lee et al, 2020;Li et al, 2021;Morzy, 2006). Bedell et al investigated which judgment is perceived first, color change or movement, and found that it depends on motion cycle (Bedell et al, 2003).…”
Section: Color and Luminance As Depth Cuesmentioning
confidence: 99%
“…In previous literature, speed and motion cues are considered for object detection and not as factors affecting depth perception (Bedell et al, 2003;Cucchiara et al, 2001;Dubuisson and Jain, 1993;Møller and Hurlbert, 1997). When accounting for speed, these works focus on sequences of frames for automatic object tracking or trajectory prediction (Chen and Meng, 2010;Lee et al, 2020;Li et al, 2021;Morzy, 2006). Self et al found that color and motion-defined shapes activate similar regions in the brain more strongly when used together than either of these cues separately (Self and Zeki, 2004).…”
Section: Color and Motion Cue Integrationmentioning
confidence: 99%